2010
DOI: 10.1007/s13139-010-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Huge Varicose Inferior Mesenteric Vein: an Unanticipated 99m Tc-labeled Red Blood Cell Scintigraphy Finding

Abstract: Ectopic varices (EcV) are enlarged portosystemic venous collaterals, which usually develop secondary to portal hypertension (PHT). Mesocaval collateral vessels are unusual pathways to decompress the portal system. Here we report the case of a huge varicose inferior mesenteric vein (IMV) that drained into perirectal collateral veins, demonstrated by (99m)Tc-labeled red blood cell (RBC) scintigraphy performed for lower gastrointestinal (GI) bleeding in a 14-year-old girl. This case illustrates the crucial role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although not included in our clinical series, many other vascular abnormalities other than aortic aneurysm may be incidentally detected on GIB scintigraphy studies, such as hemangiomas, great vessel tortuosity, varices, arteriovenous malformations, and aortaenteric fistulas ( 24 , 25 , 26 , 27 ). Clinicians should be aware that these vascular anomalies may cause false-positive results for GIB.…”
Section: Discussionmentioning
confidence: 99%
“…Although not included in our clinical series, many other vascular abnormalities other than aortic aneurysm may be incidentally detected on GIB scintigraphy studies, such as hemangiomas, great vessel tortuosity, varices, arteriovenous malformations, and aortaenteric fistulas ( 24 , 25 , 26 , 27 ). Clinicians should be aware that these vascular anomalies may cause false-positive results for GIB.…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc-labeled RBC scintigraphy is a very useful method for detecting active GI bleeding; previous studies have reported the sensitivity and specificity of 99m Tc-labeled RBC scintigraphy as 78.6-97 % and 70.4-100 %, respectively [4,5]. However, other studies have reported potential pitfalls, unanticipated and false-positive results, but most of them could be excluded because of untypical patterns of radioactivity [1,[4][5][6][7][8]. The present study could also rule out the possibility of GI bleeding.…”
mentioning
confidence: 99%